Distal Nerve Exploration in the Palm Avoids Nerve Transfer in a Posttraumatic Ulnar Nerve Injury with a Claw Hand - J. Terrence Jose Jerome (Indian Journal of Neurosurgery)
Posttraumatic low ulnar nerve injuries develop claw hand and poor hand function. Transferring the opponens pollicis branch of the thenar branch at the palm to the terminal division of the deep branch of the ulnar nerve is an effective distal nerve transfer to restore pinch in low ulnar nerve injuries. The author describes the surgical technique for a 4-month-old low ulnar nerve injury in a 25-year-old man with inconclusive electrodiagnostic findings and no clinical findings of distal nerve recovery. The intraoperative electrical stimulation of the nerve in the palm is a simple method to ensure the reinnervation of the ulnar nerve in a claw hand and muscle wasting. Therefore, all postcut injuries with a low ulnar nerve palsy with claw hands may not need a distal nerve transfer. However, performing distal nerve exploration in the palm is vital in cases of doubtful nerve recovery in a low ulnar nerve palsy with a claw hand.